Capital formation in post-socialist countries - Jacek Tomkiewicz (Transformation, Integration and Globalization Economic Research (TIGER), 2003)
Process of economic transition influences every aspect of economy. Capital formation process in post-socialist countries is very interesting. I check what are the determinants of level of investments during the transition process. I found that despite of high level of accumulation in socialist economies, capital production was not able to deliver level and structure of production which was demanded in market oriented economy.
Keywords: 330; Investition; Sparen; Systemtransformation; Polen; Ungarn; Tschechien